Investmnet Analysis portfolio Management - Reilly, Frank K. (South-Western, 2012)
The purpose of this book is to help you learn how to manage your money to derive the maximum benefit from what you earn. Mixing investment instruments and capital markets with the theoretical detail on evaluating investments and opportunities to satisfy risk-return objectives along with how investment practice and theory is influenced by globalization leaves readers with the mindset on investments to serve them well. The material is intended to be rigorous and empirical yet not overly quantitative. We continue with unparalleled international coverage, newly rewritten and reorganized derivatives material to be more intuitive and clearer, three additional chapters on derivatives pricing for those who want more detail, rewritten material on multifactor models of risk and return, and new CFA problems for more practice on computations concerning investment decisions. To manage money and investments, one needs to learn about investment alternatives and develop a way of analyzing and thinking about investments that will be of benefit and allow a foundation as new tools and investment opportunities become available. Reilly/Brown provide the best foundation, used extensively by professionals, organizations, and schools across the country. A great source for those with both a theoretical and practical need for investment expertise.